Impact of monetary policy on financial stability in good times - Peterson K. Ozili (Seonmul yeongu)
This study examines the impact of monetary policy on financial stability in good years. It focuses on the impact of three monetary policy tools on financial stability. The study used the median quantile regression method to analyze 22 countries during the 2011 to 2018 period – a period which isolates the shock from the coronavirus disease 2019 (COVID-19) pandemic and the shock from the global financial crisis. The financial stability indicator is the country-level bank nonperforming loans ratio. The monetary policy indicators are broad money growth, broad money-to-GDP ratio and the central bank interest rate, while controlling for the inflation rate, total unemployment rate, efficiency ratio, institutional governance quality and economic growth rate. The findings reveal that high central bank interest rates impair financial stability by increasing the bank nonperforming loans ratio in African countries and developing countries. In contrast, high central bank interest rates improve financial stability in developed countries and emerging market countries. Furthermore, higher broad money growth improves financial stability in European banks, while broad money growth, broad money-to-GDP ratio and central bank interest rate do not have a significant effect on the NPL ratio of Asian banks.